Retorno ao trabalho após licença-maternidade sob perspectiva das mães: um estudo descritivo e comparativo entre Brasil e Estados Unidos - Barbano, Letícia Maria (2024)
Gender equality is one of the seventeen Sustainable Development Goals (SDGs) of the United Nations (UN). Worldwide, mothers face significant penalties in the labor market compared to men and women without children. These penalties affect career progression, employment opportunities, and the ability to remain in the workforce. This scenario becomes even more challenging after maternity leave, a critical period that can determine whether mothers continue in or leave formal employment. Grounded in Occupational Science, the overall objective of this study was to identify and discuss the support that companies can offer to mothers after maternity leave, from the perspective of these women. A descriptive, comparative, and longitudinal design was used, with a quantitative-qualitative approach. The non-probabilistic sample consisted of mothers employed under the CLT regime who took paid maternity leave (Brazil) and those who took maternity leave (USA). The instruments used for data collection were: the Job Satisfaction Scale, the Turnover Intention Scale, the Perceived Organizational Support Scale, and the Family Supportive Supervisor Behaviors Scale. These instruments were applied through an electronic survey at two points: immediately after returning from maternity leave and three months after that return. A semi-structured interview was also conducted via the Zoom platform, still within the first year of return from leave, with the same participating mothers. Quantitative data were analyzed using Generalized Estimating Equations, and interviews were analyzed using Reflexive Thematic Analysis. Data were collected between February 2022 and September 2023 for Brazil and between September 2023 and July 2024 for the United States. Results indicated that company support increases job satisfaction and reduces the intention to leave employment and that mothers prefer a gradual and planned return after leave. Possible actions of Occupational Therapy are discussed from the perspective of Occupational Science.